Contrast-enhanced cross sectional imaging and capsule endoscopy: new perspectives for a whole picture of the small bowel - Carvalho, Pedro Boal (2016)
Small bowel evaluation is a challenging task and has been revolutionized by high-quality contrasted sectional imaging (CT enterography - CTE) and magnetic resonance enterography (MRE) as well as by small bowel capsule endoscopy (SBCE).The decision of which technique to employ during the investigation of small bowel diseases is not always simple or straightforward. Moreover, contraindications may preclude the use of these techniques in some patients, and although they are noninvasive procedures, may present with various complications. SBCE plays a crucial role in the investigation of both obscure gastrointestinal bleeding and Crohn's disease, but it is also useful for surveillance of patients with Peutz-Jeghers syndrome, while CTE is very accurate in small bowel tumours and in established Crohn's Disease, and its use in patients presenting with gastrointestinal bleeding is increasing. MRE, an expensive and not widely available technique, is essential for the study of patients with Crohn's Disease, and presents an attractive alternative to SBCE in Peutz-Jeghers syndrome surveillance.These diagnostic modalities are often not competitive but synergistic techniques. Knowing their characteristics, strengths and limitations, indications, contraindications and potential complications, as well as the adaptation to local availability and expertise, is essential to better select which procedures to perform in each patient, both safely and effectively, in order to optimize management and improve patient outcomes.